Correlation Between Phytoplankton and Bacteria in Pond Water with the Productivity of Vaname Shrimp Ponds (Penaeus vannamei) Cultivated with an Intensive System - M. Muhtar Mandele; Muhammad Amin; Gunanti Mahasri (Jurnal Penelitian Pendidikan IPA, 2024)
The level of pond productivity is influenced by the environmental conditions of maintenance caused by the physiochemical and biological quality of pond waters. Biological parameters of waters consist of the abundance of Phytoplankton and Bacteria. The purpose of this study was to determine the correlation between the abundance and types of Phytoplankton and Bacteria in pond water to the productivity level of whiteleg shrimp (Penaeus vannamei) ponds in different DOCs cultivated with an intensive system. The research method used observed maintenance parameters, namely the diversity and abundance of Phytoplankton including Green Algae (GA), Blue Green Algae (BGA), Diatome, and Dinoflagellate groups. Other parameters include Total Bacteria Count (TBC), Total Vibrio Count (TVC) Yellow, and Total Vibrio Count (TVC) Green. These research parameters will be subjected to Multiple Linear Regression analysis on the total harvest, feed conversion value (FCR), and survival rate (SR) of whiteleg shrimp obtained from each pond. The results of the study showed that the abundance of Phytoplankton based on the group from the lowest to the highest value was the Dinoflagellate group of 0 cells/mL with the GA group of 1.52 x 106 cells/mL. Parameters found that were significant to the level of pond productivity were the abundance of TBC and BGA (P <0.05). The conclusion is that the level of pond productivity is influenced by the abundance of Phytoplankton and bacteria based on the diversity of their species.